2021
DOI: 10.1093/jb/mvab035
|View full text |Cite
|
Sign up to set email alerts
|

Novel photochromic inhibitor for mitotic kinesin Eg5 which forms multiple isomerization states

Abstract: The mitotic kinesin Eg5 is a plus-end directed homotetrameric molecular motor essential for the formation of bipolar spindles during cell division. Kinesin Eg5 is overexpressed in cancer cells and hence considered a target for cancer therapy; the inhibitors specific for Eg5 have been developed as anti-cancer drugs. In this study, we synthesized a novel functional photoresponsive inhibitor composed of spiropyran and azobenzene derivatives to control Eg5 function with multi-stage inhibitory activity accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Monastrol as a specific compound is a protagonist of the DHPM class. Research has revealed that its action as an inhibitor on human kinesin Eg5 leads to apoptosis by mitotic spindle arrest [8][9][10][11]. Reported data show other possible targets for these molecules, such as centrin [12], calcium channels [13] and topoisomerase I [14].…”
Section: Introductionmentioning
confidence: 99%
“…Monastrol as a specific compound is a protagonist of the DHPM class. Research has revealed that its action as an inhibitor on human kinesin Eg5 leads to apoptosis by mitotic spindle arrest [8][9][10][11]. Reported data show other possible targets for these molecules, such as centrin [12], calcium channels [13] and topoisomerase I [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Tamaoki group introduced one of the first photoswitchable inhibitors of a motor protein for the mitotic kinesin CENP‐E, which was based on the small molecule GSK923295 [37, 38] . Recently, Maruta and colleagues introduced photoswitchable inhibitors that enabled reversible control of Eg5 in vitro [39–41] . However, they did not demonstrate activity in cells, possibly due to insufficient cell permeability and solubility of their compounds.…”
Section: Figurementioning
confidence: 99%
“…[37,38] Recently, Maruta and colleagues introduced photoswitchable inhibitors that enabled reversible control of Eg5 in vitro. [39][40][41] However, they did not demonstrate activity in cells, possibly due to insufficient cell permeability and solubility of their compounds. This led us to synthesize and evaluate azobenzenebased photoswitchable Eg5 inhibitors.…”
mentioning
confidence: 99%
“…These nucleotide-binding proteins might have evolved from a common nucleotidebinding ancestral protein, as they share a common catalytic core region, including the P-loop, Switch I, and Switch II, and molecular mechanisms utilizing a nucleotide hydrolysis cycle. Previously, we demonstrated that incorporating artificial regulatory nanodevices, such as photochromic molecules, into the kinesin functional site enables photoreversible regulation of ATPase activity [5][6][7] . Subsequently, we incorporated azobenzene derivatives into the functional sites of the motor domain and succeeded in photocontrolling GTPase activity 8 .…”
mentioning
confidence: 99%